Players at home: Physical activity and quality of life in 12-17 years-old football (soccer) players during the Covid-19 lockdown - Zago, M.; Lovecchio, N.; Galli, M. (International Journal of Sports Science & Coaching, 2022)
Background: Aggressive preventive actions were required to face the Covid-19 outbreak. However, from March 2020 on, many healthy youth football players have seen their sporting activities disrupted by the restrictions on outdoor exercise. This study describes physical activity and quality of life during April 2020 lockdown of young people participating in organized football. Methods: 1163 young football players aged 12-17 years (185 girls) completed a web-based questionnaire including the Youth Physical Activity and the Youth Quality of Life-Short Form Questionnaires; information on lifestyle and football-specific activity were also collected. Differences according to sex, urban/rural context and élite/non-élite club level were tested using a 2 × 2 × 2 MANOVA (age considered as a covariate). Results: We found that: (i) on average, exposure to football accounted for 3.2 hours/week, was higher in élite clubs and changed in nature, being mainly performed individually; 19% of participants practiced football <1 hour/week; (ii) only 56% of the participants reported 7 or more hours/week of moderate-to-vigorous physical activity, which decreased with age and changed according to the geographical context; (iii) perceived quality of life was lower in youth playing for non-elite clubs and in older girls; (iv) coaches, rather that official initiatives, were the primary source of football exercises practiced at home. Conclusion: A status of limited physical activity emerged; this might lead to deconditioning and susceptibility to injuries when football could restart. Governing bodies, football Associations and clubs could exploit these results to take informed decisions and support evidence-based interventions during and after the Covid-19 pandemic.